Three interval thixotropy test to determine structural regeneration of a glucomannan based hydrocolloid film at air/water interface: Interfacial, molecular, thermal and surface characterization. (December 2016) - Yilmaz, Mustafa Tahsin; Vatansever, Ceyda
Abstract: This work appears to be the first example with respect to two points: First, a film from salep, a glucomannan based hydrocolloid was formed and characterized in terms of interfacial properties. Second, three interval thixotropy test (3ITT) was applied to determine effect of instant interfacial shear stress or shear rate on deformation and regeneration of salep glucomannan (SG) films at air/water interface. In order to assess the interfacial properties, the salep from which SG films was formed was also characterized in terms of compositional, molecular, thermal and surface properties. To determine interfacial properties, the SG films prepared at different concentrations (2–3%) were formed at the water/air interface. Amplitude and frequency sweeps were applied to characterize the structure of the films at equilibrium, revealing a gel-like structure of the SG films at equilibrium. 3ITT revealed that shear rate/stress levels at different concentrations resulted in a remarkable deformation in SG films whereas they were fully recoverable, showing regeneration after distortion by a steady shear flow, as demonstrated by decreasing deformation percentage ( D r ) values and increasing time required for the recovery ( R time ) values at increasing concentrations. 3ITT appeared to be an effective tool to simulate and analyze effects of real pumping, mixing and instant stirring processes during production and handling steps of SG films. The SG films were proven to have improved interfacial properties, which suggests that they may be an alternative to other hydrocolloid based films in terms of adsorbing onto air-water interfaces to reduce surface and interfacial tensions. Graphical abstract: Highlights: A glucomannan based film was formed from salep glucomannan. Salep was characterized in terms of molecular, thermal and surface properties. Three interval thixotropy test revealed a gel-like structure of the glucomannan films. Salep glucomannan films were fully recoverable, showing regeneration. Salep glucomannan films were proven to have improved interfacial properties.